2022
DOI: 10.55782/ane-2022-026
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin alleviates experimental autoimmune encephalomyelitis by suppressing Th1 and Th17 cells and upregulating Th2 and regulatory T cells

Abstract: Multiple sclerosis (MS) is the most typical chronic inflammatory, autoimmune demyelinating disease of the central nervous system (CNS) which leads to physical dysfunction and paralysis in patients. A commonly used animal model for this disease is experimental autoimmune encephalomyelitis (EAE). Daphnetin (7,8‑dihydroxycoumarin) has been reported to exert various pharmacological activities, such as being neuroprotective and anti‑inflammatory, together with having antioxidant, anticancer, and antiviral propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“… 86 More recently, an increase in the production of IL‐17 is also observed in lymphocytes derived from mice with EAE. 86 , 87 Consistent with these observations, IL‐17 transcript is upregulated in MS lesion 62 and MS activity is correlated with an increased number of Th17 cells in the patient's blood. 88 The pathogenic effect of Th17 in the EAE model is further confirmed by findings that deficiency or neutralization of IL‐17A delays the onset and reduces the incidence and severity of relapses.…”
Section: Role Of Th17 Cells In the Pathogenesis Of Mssupporting
confidence: 55%
See 1 more Smart Citation
“… 86 More recently, an increase in the production of IL‐17 is also observed in lymphocytes derived from mice with EAE. 86 , 87 Consistent with these observations, IL‐17 transcript is upregulated in MS lesion 62 and MS activity is correlated with an increased number of Th17 cells in the patient's blood. 88 The pathogenic effect of Th17 in the EAE model is further confirmed by findings that deficiency or neutralization of IL‐17A delays the onset and reduces the incidence and severity of relapses.…”
Section: Role Of Th17 Cells In the Pathogenesis Of Mssupporting
confidence: 55%
“…Further evidence demonstrated that augmented expression of IL‐17 was observed in patients in both brain lesions and mononuclear cells isolated from blood and cerebrospinal fluids 86 . More recently, an increase in the production of IL‐17 is also observed in lymphocytes derived from mice with EAE 86,87 . Consistent with these observations, IL‐17 transcript is upregulated in MS lesion 62 and MS activity is correlated with an increased number of Th17 cells in the patient's blood 88 .…”
Section: Role Of Th17 Cells In the Pathogenesis Of Msmentioning
confidence: 63%
“…The mice were subcutaneously injected at the flanks, with 250 μg synthetic MOG35–55 (BioBasic, Markham, ON, Canada), which was emulsified with Complete Freund’s Adjuvant (Sigma Aldrich, St. Louis, MO, USA) containing 4 mg/mL of Mycobacterium tuberculosis H37RA (Difco Laboratories, Detroit, MI, USA) [ 19 , 20 ]. Mice also received 250 ng Pertussis toxin (Sigma-Aldrich, St. Louis, MO, USA) intraperitoneally, both simultaneously with EAE induction and 48 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, daphnetin suppressed the activation of microglia, astrocytes, and neurons, thus reducing the nociceptive sensitization in neuropathic pain rats ( Zhang et al, 2023 ). In addition, in an experimental autoimmune encephalomyelitis (EAE) mice model, daphnetin (2 and 8 mg/kg) treatment significantly decreased lymphocyte infiltration and demyelination, which was attributed to reduction in pro-inflammatory factors, including TNF-α and IL-17 and an increase in anti-inflammatory factors, such as IL-4 and IL-10 ( Soltanmohammadi et al, 2022 ). Evidence showed that daphnetin ameliorated the progress of hepatocellular carcinoma by reducing inflammation ( Li et al, 2022 ).…”
Section: Effects Of Daphnetin On Inflammatory Factorsmentioning
confidence: 99%